E.U. paediatric MOG consortium consensus: Part 2 – Neuroimaging features of paediatric myelin oligodendrocyte glycoprotein antibody-associated disorders. (November 2020) - Baumann, Matthias; Bartels, Frederik; Finke, Carsten; Adamsbaum, Catherine; Hacohen, Yael; Rostásy, Kevin; Mog consortium, E.U. paediatric; Bruijstens, Arlette L.; Wendel, Eva-Maria; Lechner, Christian; Breu, Markus; et al.
Abstract: Imaging plays a crucial role in differentiating the spectrum of paediatric acquired demyelinating syndromes (ADS), which apart from myelin oligodendrocyte glycoprotein antibody associated disorders (MOGAD) includes paediatric multiple sclerosis (MS), aquaporin-4 antibody neuromyelitis optica spectrum disorders (NMOSD) and unclassified patients with both monophasic and relapsing ADS. In contrast to the imaging characteristics of children with MS, children with MOGAD present with diverse imaging patterns which correlate with the main demyelinating phenotypes as well as age at presentation. In this review we describe the common neuroradiological features of children with MOGAD such as acute disseminated encephalomyelitis, optic neuritis, transverse myelitis, AQP4 negative NMOSD. In addition, we report newly recognized presentations also associated with MOG-ab such as the 'leukodystophy-like' phenotype and autoimmune encephalitis with predominant involvement of cortical and deep grey matter structures. We further delineate the features, which may help to distinguish MOGAD from other ADS and discuss the future role of MR-imaging in regards to treatment decisions and prognosis in children with MOGAD. Finally, we propose an MRI protocol for routine examination and discuss new imaging techniques, which may help to better understand the neurobiology of MOGAD. Highlights: Children with MOGAD present with typical imaging patterns. Imaging patterns are associated with clinical phenotypes and age at presentation. Unusual imaging features include leukodystrophy-like or predominant cortical lesions. In contrast to other acquired demyelinating syndromes, lesions usually resolve. New imaging techniques may aid to understand the neurobiology and varying outcomes.